A light- and electron-microscopic study on a vesicular-arbuscular host-fungus interaction in gametophytes and young sporophytes of the Gleicheniaceae (Filicales) - Schmid, Elfi (The New phytologist, 1995)
Gametophytes and primary roots of young sporophytes of the Gleicheniaceae were studied by means of light- and electron microscopy. An aseptate fungus invaded the gametophyte tissue through the rhizoids. The fungus spread within the thickened midrib forming intracellular hyphal coils. The latter gave rise regularly to arbuscules which were cytoplasmic in the young part of the midrib. In the older midrib, arbuscules degenerated and vesicles occurred. With arbuscular development, host cytoplasm and cell organelles increased and starch disappeared from plastids. The fungus formed globose spores inside the rhizoids. The gametophyte fungus did not transverse the gametophyte- sporophyte junction. Primary roots shorter than 2 mm were not infected. Primary roots longer than 2 mm showed vesicular-arbuscular mycorrhiza with a completely intracellular development of the fungus